Is nitrogen transfer among plants enhanced by contrasting nutrient-acquisition strategies? - Teste, F.; Veneklaas, E.; Dixon, Kingsley; Lambers, H. (Wiley-Blackwell Publishing Ltd., 2015)
Nitrogen (N) transfer among plants has been found where at least one plant can fix N2. In nutrient-poor soils, where plants with contrasting nutrient-acquisition strategies (without N2 fixation) co-occur, it is unclear if N transfer exists and what promotes it. A novel multi-species microcosm pot experiment was conducted to quantify N transfer between arbuscular mycorrhizal (AM), ectomycorrhizal (EM), dual AM/EM, and non-mycorrhizal cluster-rooted plants in nutrient-poor soils with mycorrhizal mesh barriers. We foliarfed plants with a K15NO3 solution to quantify one-way N transfer from ‘donor’ to ‘receiver’ plants. We also quantified mycorrhizal colonization and root intermingling. Transfer of N between plants with contrasting nutrient-acquisition strategies occurred at both low and high soil nutrient levels with or without root intermingling. The magnitude of N transfer was relatively high (representing 4% of donor plant N) given the lack of N2 fixation. Receiver plants forming ectomycorrhizas or cluster roots were more enriched compared with AM-only plants. We demonstrate N transfer between plants of contrasting nutrient-acquisition strategies, and a preferential enrichment of cluster-rooted and EM plants compared with AM plants. Nutrient exchanges among plants are potentially important in promoting plant coexistence in nutrient-poor soils.